Post-traumatic people in Paul Auster's The Book of Illusions from Cathy Caruth's and Michelle Balaev's perspectives - Samira Sasani; Diba Arjmandi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
In his novel The Book of Illusions, Paul Auster displays his knowledge not only as a writer, but also as a talented critic of cinema, painting and world literature. Opening up the question of identity after the loss, Auster presents the reader with the traumatic form of grief over the dead ones. The trauma which is portrayed in The Book of Illusions is the direct experience with death, with those who are left behind and for those who find death as the only solution for being forgiven. Strangely enough, while the main theme is death, Auster portrays the ways of resistance and the power of love to shape the process of post-traumatic identification. Precisely the aim here is to analyze Austerâ€™s novel with the help of new theories that are introduced recently into the realm of literary criticism and trauma studies by Cathy Caruth and Michelle Balaev. By studying different opinions about loss and trauma and applying new perspectives, this research scrutinizes Austerian characters. Therefore there is a survey, a study of trauma from vantage points of traditional model theoreticians like Caruth and also pluralistic model argument represented by Balaev. Â  Keywords: Paul Auster; The Book of Illusions; Trauma Theory; Cathy Caruth; Michelle Balaev